Additively manufactured iron-manganese for biodegradable porous load-bearing bone scaffold applications. (February 2020) - Carluccio, Danilo; Xu, Chun; Venezuela, Jeffrey; Cao, Yuxue; Kent, Damon; Bermingham, Michael; Demir, Ali Gökhan; Previtali, Barbara; Ye, Qingsong; Dargusch, Matthew
Abstract: Selective laser melting (SLM) can produce complex hierarchical architectures paving the way for highly customisable biodegradable load-bearing bone scaffolds. For the first time, an in-depth analysis on the performance of SLM-manufactured iron-manganese bone scaffolds suitable for load-bearing applications is presented. Microstructural, mechanical, corrosion and biological characterisations were performed on SLM-manufactured iron-manganese scaffolds. The microstructure of the scaffold consisted primarily of γ-austenite, leading to high ductility. The mechanical properties of the scaffold were sufficient for load-bearing applications even after 28 days immersion in simulated body fluids. Corrosion tests showed that the corrosion rate was much higher than bulk pure iron, attributed to a combination of the manufacturing method, the addition of Mn to the alloy and the design of the scaffold. In vitro cell testing showed that the scaffold had good biocompatibility and viability towards mammalian cells. Furthermore, the presence of filopodia showed good osteoblast adhesion. In vivo analysis showed successful bone integration with the scaffold, with new bone formation observed after 4 weeks of implantation. Overall the SLM manufactured porous Fe-35Mn implants showed promise for biodegradable load-bearing bone scaffold applications. Statement of significance: Biodegradable iron scaffolds are emerging as a promising treatment for critical bone defects. Within this field, selective laser melting (SLM) has become a popular method of manufacturing bespoke scaffolds. There is limited knowledge on SLM-manufactured iron bone scaffolds, and no knowledge on their application for load-bearing situations. The current manuscript is the first study to characterise SLM manufactured iron-manganese bone scaffolds for load-bearing applications and also the first study to perform In vivo testing on SLM produced biodegradable iron scaffolds. In this study, for the first time, the mechanical, corrosion and biological properties of an iron-manganese scaffold manufactured using SLM were investigated. In summary the SLM-manufactured porous iron-manganese implants displayed great potential for biodegradable load-bearing bone scaffolds. Graphical abstract: Image, graphical abstract